Exploring Students' Academic Achievement in Basketball Learning: Simple Game Modifications for Primary School Students - Budi, Agung Prasetyo; La Kamadi; Haeruddin, Sofyan (ETDC: Indonesian Journal of Research and Educational Review, 2022)
Research on the use of simple games as modifications in basketball materials aims to make it easier for students to practice basketball at Mi plus Raudlatul Muta'allimin. The available methods are very limited with the number of students, as many as 35 people in class V, making learning with basketball materials a little difficult. The data collection method used is the questionnaire method. The data analysis technique used is quantitative descriptive data analysis. Based on the results of data analysis shows that there is a decrease in student academic achievement in learning basketball by -6.58%. So it can be said that there is no effect of modified basketball game on student achievement in basketball learning. In addition, the results of hypothesis testing show that the value of Sig = 1.019 ≥ α = 0.05. This means that H0 is accepted and Ha is rejected, so that there is no effect of the modified basketball game on the academic achievement of the fifth-grade students of MI Plus Raudlatul Muta'allimin. As a suggestion, further research is needed on the effect of modified basketball games on academic achievement in basketball learning.